2015
DOI: 10.4018/ijkm.2015010104
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Knowledge Enablers and Project Success in IT Organizations

Abstract: Knowledge enablers exist at the organizational and project levels. There is however, no meaningful means to measure organizational or project knowledge sharing. The need to understand the elements that enable this flow of knowledge is dramatically evidenced in information technology organizations in which insufficient knowledge sharing leads to intellectual capital loss, rework, skills deterioration, and repeated mistakes that increase project costs or failures. The goal of this study was to examine the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 60 publications
(94 reference statements)
0
0
0
Order By: Relevance
“…Recent studies have shown increased attention to KS in organisations (Arain et al, 2018;Lotfi et. al, 2016;McKay et al, 2015;Ramayah et al, 2013;Ranasinghe et al, 2013;Ganguly et al, 2011;Jeon et.al, 2011;Wang & Noe, 2010;Hsu & Lin;Cabrera et al, 2006;Peltokorpi, 2006;Ipe,2003). In addition, KS studies have expanded their research focus to include professional groups such as academicians (Fullwood et al, 2019;Ramayah et al, 2013), accountants (Phang & Foong, 2010), civil and mechanical engineers (Matzler et al, 2008), librarians (Noaman & Fouad, 2014) and healthcare practitioners (Razzaque et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown increased attention to KS in organisations (Arain et al, 2018;Lotfi et. al, 2016;McKay et al, 2015;Ramayah et al, 2013;Ranasinghe et al, 2013;Ganguly et al, 2011;Jeon et.al, 2011;Wang & Noe, 2010;Hsu & Lin;Cabrera et al, 2006;Peltokorpi, 2006;Ipe,2003). In addition, KS studies have expanded their research focus to include professional groups such as academicians (Fullwood et al, 2019;Ramayah et al, 2013), accountants (Phang & Foong, 2010), civil and mechanical engineers (Matzler et al, 2008), librarians (Noaman & Fouad, 2014) and healthcare practitioners (Razzaque et al, 2013).…”
Section: Introductionmentioning
confidence: 99%